An antibacterial, antioxidant and hemostatic hydrogel accelerates infectious wound healing - Ziyi Zhou; Dengjun Zhang; Xuchao Ning; Linbo Jin; Yijing Lin; Chen Liang; Xin Wen; Tianhao Huang; Junli Zhou; Yiming Zhang (Journal of Nanobiotechnology)
Abstract Hydrogel drug-delivery system that can effectively load antibacterial drugs, realize the in-situ drug release in the microenvironment of wound infection to promote wound healing. In this study, a multifunctional hydrogel drug delivery system (HA@TA-Okra) was constructed through the integration of hyaluronic acid methacrylate (HAMA) matrix with tannic acid (TA) and okra extract. The composition and structural characteristics of HA@TA-Okra system and its unique advantages in the treatment of diverse wounds were systematically evaluated. TA, due to its unique chemical structure, is able to anchor within the HAMA network through interactions and cross-linking, conferring exceptional mechanical strength and stability to the hydrogel. Both TA and okra extract possess antioxidant and antibacterial properties, and when they two acts synergistically they can effectively scavenge free radicals, enhance antibacterial action, diminishing the risk of wound infection. In vitro experiments revealed that HA@TA-Okra system has superior properties, such as rapid gel response, remarkable swelling regulation, and potent antioxidant ability. Furthermore, the HA@TA-Okra system significantly outperformed conventional dressings in terms of hemostatic performance in a rat hemorrhage model. We further evaluated the repair role of HA@TA-Okra system in vivo by establishing an animal model of full-thickness skin defects and a model of infected total skin defects. The results confirmed its positive effects in fighting bacterial infection, reducing inflammation and promoting wound healing. In summary, the HA@TA-Okra system exhibits comprehensive properties such as antibacterial, antioxidant and hemostatic properties, which has a potential application in the field of tissue repair medicine. Graphical Abstract